421 Intrapelvic Protrusion of a Femoral Head in A Ceramic-on-Ceramic Total Hip Replacement, A Case Report. (4th May 2021) - Altell, T; Massa, E; Edwards, M
Abstract: Introduction: Ceramic on ceramic bearing in Total Hip Replacement (THR) is associated with a low but evident risk of ceramic linear fracture, which can lead to catastrophic failure if not diagnosed and treated early. Case presentation: A 59-year-old male patient, who underwent a ceramic-on-ceramic THR 8 years ago, presented to our centre with a five-week history of right hip pain, after he suddenly twisted his upper body and felt a sharp pain in his groin. Prior to the injury he had an excellent functional level with the prosthesis. His examination findings confirmed a reduced range of movement with pain in the groin on internal and external rotation. X-ray and CT of the hip confirmed a ceramic liner fracture with protrusion of the femoral head into the pelvis. A revision THR was subsequently performed. Discussion: The usual pattern of liner fracture in this type of bearings is that the femoral head stays contained inside the metal cup. In our case, the ceramic femoral head uniquely fractured the liner and passed into the pelvis. To the best of our knowledge, this is the third reported case in literature where a ceramic femoral head protrudes through the metal cup into the pelvis.